Is it possible to detect planets around young active G and K dwarfs?. Issue 4 (24th January 2014) - Jeffers, S. V.; Barnes, J. R.; Jones, H. R. A.; Reiners, A.; Pinfield, D. J.; Marsden, S. C.
Abstract: Theoretical predictions suggest that the distribution of planets in very young stars could be very different to that typically observed in Gyr old systems that are the current focus of radial velocity surveys. However, the detection of planets around young stars is hampered by the increased stellar activity associated with young stars, the signatures of which can bias the detection of planets. In this paper, we place realistic limitations on the possibilities for detecting planets around young active G and K dwarfs. The models of stellar activity based on tomographic imaging of the G dwarf HD 141943 and the K1 dwarf AB Dor also include contributions from plage and many small random starspots. Our results show that the increased stellar activity levels present on young solar-type stars strongly impacts the detection of Earth-mass and Jupiter-mass planets and that the degree of activity jitter is directly correlated with stellar v  sin  i . We also show that for G and K dwarfs, the distribution of activity in individual stars is more important than the differences in induced radial velocities as a function of spectral type. We conclude that Jupiter-mass planets can be detected close-in around fast-rotating young active stars, Neptune-mass planets around moderate rotators and that Super-Earths are only detectable around very slowly rotating stars. The effects of an increase in stellar activity jitter by observing younger stars can be compensated for by extending the observational base-line to at least 100 epochs.